What counts as a voiceable concern in decisions about speaking out in hospitals: A qualitative study. Issue 2 (April 2022) - Dixon-Woods, Mary; Aveling, Emma L; Campbell, Anne; Ansari, Akbar; Tarrant, Carolyn; Willars, Janet; Pronovost, Peter; Mitchell, Imogen; Bates, David W; Dankers, Christian; McGowan, James; Martin, Graham
Objectives: Those who work in health care organisations are a potentially valuable source of information about safety concerns, yet failures of voice are persistent. We propose the concept of 'voiceable concern' and offer an empirical exploration. Methods: We conducted a qualitative study involving 165 semi-structured interviews with a range of staff (clinical, non-clinical and at different hierarchical levels) in three hospitals in two countries. Analysis was based on the constant comparative method. Results: Our analysis shows that identifying what counts as a concern, and what counts as a occasion for voice by a given individual, is not a straightforward matter of applying objective criteria. It instead often involves discretionary judgement, exercised in highly specific organisational and cultural contexts. We identified four influences that shape whether incidents, events and patterns were classified as voiceable concerns: certainty that something is wrong and is an occasion for voice; system versus conduct concerns, forgivability and normalisation. Determining what counted as a voiceable concern is not a simple function of the features of the concern; also important is whether the person who noticed the concern felt it was voiceable by them. Conclusions: Understanding how those who work in health care organisations come to recognise what counts as a voiceable concern is critical to understanding decisions and actions about speaking out. The concept of a voiceable concern may help to explain aspects of voice behaviour in organisations as well as informing interventions to improve voice.